Psicología, política y poesía en República IV y X - Soares, Lucas (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
In this paper, I argue that in the Republic the possibility of a good koinōnia is hindered by the emotional potency and psychological perversion of mimetic-pleasurable poetry, which stimulates and strengthens the irrational part of the soul of its recipients through the imitation of characters linked to desire and anger. To this end, I examine, first, some of the passages in Republic IV in which it is possible to subscribe to the priority of the psychic tripartition over the political tripartition. Secondly, I point out some of the central features of the psychological critique of mimetic-pleasurable poetry in Republic X.

En este artículo me interesa sostener que en la República la posibilidad de una buena koinōnía se ve obstaculizada por la potencia emocional y perversión psicológica de la poesía mimético-placentera, la cual estimula y fortalece la parte irracional del alma de sus receptores mediante la imitación de personajes ligados al deseo y la ira. Para tal fin examino, en primer lugar, algunos de los pasajes de República IV en los que es posible suscribir la prioridad que tiene la tripartición psíquica por sobre la tripartición política. En segundo lugar, señalo algunos de los rasgos centrales de la crítica psicológica de la poesía mimético-placentera en República X.
Psychology, politics and poetry in Republic IV and X
Keywords: Psychology; Politics; Poetry; Koinōnia; Republic; Psicología; Política; Poesía; Koinōnía; República; https://purl.org/pe-repo/ocde/ford#6.03.01